LIBRARIAN-COMPUTER INTERACTION: A STUDY ON THE EFFECTS OF OFFICE AUTOMATION ON LIBRARIANS OF BABY BOOMERS, GENERATION X AND GENERATION Y - , Ida Fajar Priyanto ([Yogyakarta] : Gadjah Mada University Library, 2011)
Abstract This decade is so unique at Gadjah Mada University Library due to the characteristics of librarians and library users. While the library users are mostly born as Generation Y (born after 1980s)